Understanding the preference for homebirth; an exploration of key barriers to facility delivery in rural Tanzania - Fabiola Moshi; Tumaini Nyamhanga (BMC, 2017)
Abstract Background There is limited information on the effect of expectant parents' socio-cultural perceptions and practices on the use of skilled birth attendants (SBAs) in rural Tanzania. The purpose of this study was to explore the socio-cultural barriers to health facility birth and SBA among parents choosing home birth in rural Tanzania, specifically in the Rukwa Region. Methods This study used a descriptive exploratory methodology. Purposive sampling was used to recruit study participants for both in-depth interviews (IDIs) and focused group discussions (FGDs). Qualitative research methods, including FGDs and IDIs, were utilized in data collection. The respondents were men and women whose youngest child had been born at home within the prior 12 months. A thematic approach was used for data analysis. Results The main themes that emerged regarding barriers to the use of health facility were 1) limited decision-making by men on place of delivery; 2) low risk perception by men and its interference with health facility birth; 3) men's limited resource mobilization for health facility birth and 4) females' perceptions that pregnancy and childbirth are low-risk events. Conclusion This qualitative study demonstrates that apart from well-documented structural barriers to skilled birth attendance in rural Tanzania, the low risk perception among both men and women plays a substantial role. The low risk perception among both men and women affects the use of SBAs in two ways. First, women become negligent and take risk of delivering at home. Second, male partners do not seriously mobilize resources for health facility childbirth. These findings reinforce the urgent need to implement creative programs to increase genuine male participation in facilitation of health facility childbirth.